Syndication networks and company survival: evidence from European venture capital deals. Issue 2 (3rd April 2022) - Christopoulos, Dimitris; Koeppl, Stefan; Köppl-Turyna, Monika
ABSTRACT: This study investigates the phenomenon of syndication in the venture capital industry. Investments conducted by syndicates are believed to have a better chance of being successful, which can be measured by the survival probability of portfolio companies or by successful exits. Using a novel and large dataset covering several countries, our analysis shows that investors' strong network ties are associated with the success of portfolio companies in Europe. We also demonstrate differences in the association of network centrality with survival between different financing rounds, with the former being more important in early-stage investments and in the first round of financing. Furthermore, we show a strong association of investors' network ties with the sales growth of portfolio companies before and after the deal, which is consistent in both selection and value-added channels. Finally, we explicitly account for the endogeneity of syndicate formation and show that the results hold if we instrument for venture firms' network properties, as indicated by significant and correspondingly larger coefficients.